Association between endothelial microparticles and objectively measured physical activity in adults with obesity - Chen Zheng; Yalan Wu; Stephen Heung-Sang Wong; Xiao Yu Tian (Advanced Exercise and Health Science)
Background: Cardiovascular disease (CVD) is a serious global public health concern that often originates from endothelial dysfunction. Microparticles (MPs) can reflect alterations in tissue or cell function phenotype and responsiveness under various physiological and pathological conditions. MPs derived from endothelial cells may serve as potential biomarkers for CVD. We investigated the association between endothelial-derived MPs (EMPs) and objectively measured physical activity (PA) in adults with obesity and their potential correlation with inflammatory and cardiometabolic biomarkers. Methods: This cross-sectional study included 50 participants, whose daily movement behaviors were evaluated using activPAL™, which measures moderate-to-vigorous intensity PA (MVPA), light PA (LPA), and standing time. The MP sub-populations were separated from platelet-poor plasma, incubated with multiple antibodies, and analyzed using multi-color flow cytometry. Cytokines, interleukin (IL)−1β, IL-8, E-selectin, P-selectin, and intercellular adhesion molecules (ICAMs), were measured using a customized Luminex® assay kit. Pearson’s correlation coefficients were used to examine associations. Results: MVPA was associated with lower expressions of ICAM and E-selectin in EMPs, whereas standing time was associated with a higher expression of E-selectin. A positive association exists between leukocyte-derived MP percentage and P-selectin levels in EMPs and E-selectin levels in the plasma. In addition, higher plasma P-selectin level was associated with higher P- and E-selectin levels in EMPs, as was higher inflammation (IL-1β and IL-8). Conclusion: The MPs were negatively associated with MVPA and positively associated with standing time in the participants with obesity. These results underscore the importance of promoting PA interventions, especially at moderate-to-vigorous intensities. Further longitudinal and interventional studies are warranted to elucidate the dynamic interplay among PA, MPs, and endothelial function.